2019
DOI: 10.1111/jcmm.14575
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA TNK2‐AS1 regulated ox‐LDL‐stimulated HASMC proliferation and migration via modulating VEGFA and FGF1 expression by sponging miR‐150‐5p

Abstract: Long non‐coding RNAs (lncRNAs) have been indicated for the regulatory roles in cardiovascular diseases. This study determined the expression of lncRNA TNK2 antisense RNA 1 (TNK2‐AS1) in oxidized low‐density lipoprotein (ox‐LDL)‐stimulated human aortic smooth muscle cells (HASMCs) and examined the mechanistic role of TNK2‐AS1 in the proliferation and migration of HASMCs. Our results demonstrated that ox‐LDL promoted HASMC proliferation and migration, and the enhanced proliferation and migration in ox‐LDL‐treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 36 publications
(66 reference statements)
1
21
0
Order By: Relevance
“…Another research by Liang et al 26 identified the lncRNA 2810403D21Rik/Mirf can act as a ceRNA of miRNA26a in ischemic myocardial injury. The lncRNA TNK-AS1 regulates smooth muscle cell proliferation and migration via acting as a ceRNA of miR-150-5p 27 . The uncovering of the ceRNA mechanism may provide a new layer for exploring the physiopathology process and shed new light on cardiovascular research.…”
Section: Discussionmentioning
confidence: 99%
“…Another research by Liang et al 26 identified the lncRNA 2810403D21Rik/Mirf can act as a ceRNA of miRNA26a in ischemic myocardial injury. The lncRNA TNK-AS1 regulates smooth muscle cell proliferation and migration via acting as a ceRNA of miR-150-5p 27 . The uncovering of the ceRNA mechanism may provide a new layer for exploring the physiopathology process and shed new light on cardiovascular research.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39][40] However, report also indicates that ox-LDL can enhance cell proliferation in human aortic smooth muscle cells or Endothelial cell at a relatively low concentration. [41][42][43][44] This difference might be due to cell performance differs to cell type when expose to ox-LDL. Additionally, Zhu et al suggest that ox-LDL plays dual effect on inflammatory response by triggering LOX-1/PPARγ pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the upstream mechanism of FGF1 dysregulation in VSMCs has been gradually elucidated. For example, in ox-LDL-treated human aortic smooth muscle cells (HASMCs), the overexpression of lncRNA TNK2-AS1 indirectly upregulates the expression levels of vascular endothelial growth factor A and FGF1 by inhibiting miR-150-5p, and thus enhances the proliferation and migration of HASMCs [ 22 ]. In this work, we found the expression of FGF1 in ox-LDL-stimulated VSMCs and carotid smooth muscle derived from ApoE −/− mice fed a high-fat diet was remarkably increased.…”
Section: Discussionmentioning
confidence: 99%